Conservation of Nematocida microsporidia gene expression and host response in Caenorhabditis nematodes - Yin Chen Wan; Emily R. Troemel; Aaron W. Reinke (PLoS ONE, 2022)
Microsporidia are obligate intracellular parasites that are known to infect most types of animals. Many species of microsporidia can infect multiple related hosts, but it is not known if microsporidia express different genes depending upon which host species is infected or if the host response to infection is specific to each microsporidia species. To address these questions, we took advantage of two species of Nematocida microsporidia, N. parisii and N. ausubeli, that infect two species of Caenorhabditis nematodes, C. elegans and C. briggsae. We performed RNA-seq at several time points for each host infected with either microsporidia species. We observed that Nematocida transcription was largely independent of its host. We also observed that the host transcriptional response was similar when infected with either microsporidia species. Finally, we analyzed if the host response to microsporidia infection was conserved across host species. We observed that although many of the genes upregulated in response to infection are not direct orthologs, the same expanded gene families are upregulated in both Caenorhabditis hosts. Together our results describe the transcriptional interactions of Nematocida infection in Caenorhabditis hosts and demonstrate that these responses are evolutionarily conserved.